Pemahaman Dan Kepedulian Implementasi Akuntansi Lingkungan Oleh UMKM Makanan Dan Minuman Di Kantin UMRI (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to determine the level of understanding and concern of food and beverage canteen MSME business actors at Muhammadiyah University of Riau regarding the application of environmental accounting in their business operations. Environmental accounting is a field of accounting that is developing by voluntarily including environmental costs in company financial reports. Research data was collected through questionnaires. Using a random proportional technique, three canteen MSMEs selling food and drinks at the Muhammadiyah University of Riau were selected. In this qualitative descriptive research, data analysis was carried out using the Miles and Huberman data analysis model in Sugiyono (2017): reducing data, presenting data, and making conclusions. The research results show that two out of three food and beverage MSME business owners in the Muhammadiyah University of Riau canteen have a good understanding and concern about the importance of implementing green accounting (environmental accounting). They do not yet understand the details of business and environmental costs, but they know that environmental costs are included in their business financial statements.